Pakistan: The real picture - Rizwana Zahid ahmed, Andrew (Ferozsons (Pvt) Limited ; Lahore, 2019)
Pakistan: The Real Picture provides an in-depth exploration of Pakistan$1 (Bs history, culture, and achievements, offering a balanced and authentic perspective on the nation.s